Plasma phospholipid long-chain n-3 polyunsaturated fatty acids and body weight change. - Jakobsen, M; Dethlefsen, C; Due, K; Slimani, N; Chajès, V; May, A; Sørensen, T; Halkjær, J; Tjønneland, A; Clavel-Chapelon, F; Boutron-Ruault, M; Fagherazzi, G; et al. (2011)
OBJECTIVE: We investigated the association between the proportion of long-chain n-3 polyunsaturated fatty acids (PUFA) in plasma phospholipids from blood samples drawn at enrollment and subsequent change in body weight. Sex, age, and BMI were considered as potential effect modifiers. METHOD: A total of 1,998 women and men participating in the European Prospective Investigation into Cancer and Nutrition (EPIC) were followed for a median of 4.9 years. The associations between the proportion of plasma phospholipid long-chain n-3 PUFA and change in weight were investigated using mixed-effect linear regression. RESULTS: The proportion of long-chain n-3 PUFA was not associated with change in weight. Among all participants, the 1-year weight change was -0.7 g per 1% point higher long-chain n-3 PUFA level (95% confidence interval: -20.7 to 19.3). The results when stratified by sex, age, or BMI groups were not systematically different. CONCLUSION: The results of this study suggest that the proportion of long-chain n-3 PUFA in plasma phospholipids is not associated with subsequent change in body weight within the range of exposure in the general population.